A Vessel-Specific Analysis of Deferred Lesions Using the Instantaneous Wave-Free Ratio and Fractional Flow Reserve - Berntorp, Karolina, MD; Mohammad, Moman A., MD, PhD; Koul, Sasha, MD, PhD; Yndigegn, Troels, MD, PhD; Fröbert, Ole, MD, PhD; Myredal, Anna, MD, PhD; Persson, Jonas, MD, PhD; Erlinge, David, MD, PhD; Götberg, Matthias, MD, PhD (Journal of the Society for Cardiovascular Angiography & Interventions, 2025)
AbstractBackgroundPhysiologically guided revascularization improves clinical outcomes. The cutoff values for deferral with fractional flow reserve (FFR) and instantaneous wave-free ratio (iFR) are the same across all coronary arteries, despite differences in coronary flow patterns. The objective was to compare deferral rates using either FFR or iFR in the right coronary artery (RCA), left anterior descending artery (LAD), and left circumflex artery (LCx), and compare clinical outcomes in deferred lesions in the RCA, LAD, and LCx. MethodsRight coronary artery, LAD, and LCx lesions in the Swedish Web-System for Enhancement and Development of Evidence-Based Care in Heart Disease Evaluated According to Recommended Therapies registry that were evaluated using either FFR or iFR were included. The composite of major adverse cardiac events (MACE) within 5 years and the individual components of cardiovascular death, noncardiovascular death, myocardial infarction, target segment revascularization, and target vessel revascularization were analyzed. ResultsIn total, 33,241 lesions were included in the final analysis (RCA, 17.8%; LAD, 62.3%; and LCx, 19.9%). The median follow-up time was 3.4 years. The median age was 69 years, and 73.5% of patients were men. The deferral rates with iFR were 10.6% higher ( P < .001) in all coronary arteries combined, 18.7% higher ( P < .001) in the RCA, 9.5% higher in the LAD ( P < .001), and 5.3% higher in the LCx ( P = .007). No significant differences were observed in the MACE rate or its individual components at 5 years between the deferred FFR and iFR groups in any of the investigated vessels. ConclusionsInstantaneous wave-free ratio demonstrated a higher deferral rate across all coronary arteries than those examined with FFR, which was especially pronounced in the RCA, without any associated increased risk of MACE.